A Naturalistic Evaluation of Group Integrative Adapt Therapy (IAT-G) with Rohingya Refugees During the Emergency Phase of a Mass Humanitarian Crisis in Cox's Bazar, Bangladesh. (August 2021) - Tay, Alvin Kuowei; Miah, Mohammad Abdul Awal; Khan, Sanjida; Mohsin, Mohammed; Alam, A.N.M. Mahmudul; Ozen, Sanem; Mahmuda, Mahmuda; Ahmed, Helal U.; Silove, Derrick; Ventevogel, Peter
ABSTRACT: Background : Studies of scalable psychological interventions in humanitarian setting are usually carried out when the acute emergency has stabilized. We report the first evaluation of an evidence-based group psychological intervention, Group Integrative Adapt Therapy (IAT-G), during the emergency phase of a mass humanitarian crisis amongst Rohingya refugees in Cox's Bazar, Bangladesh. Methods : We did a pragmatic naturalistic evaluation (2018-2020) of a seven-session group intervention with adult Rohingya refugees with elevated symptoms of depression (≥10 on the Patient Health Questionnaire) and/or posttraumatic stress disorder, PTSD, (≥3 on the Posttraumatic Stress Disorder-8), and functional impairment (≥17 on WHO Disability Assessment Schedule or WHODAS-brief). Screening was done across the most densely populated campsites. Blind assessments were completed at baseline, posttreatment, and at 3-month follow-up using culturally adapted measures of depression, anxiety, posttraumatic stress symptoms, complicated bereavement, adaptive stress associated with disrupted psychosocial support systems, functional impairment, and resilience. Findings : 383 persons were screened and of the 144 persons who met inclusion criteria all participated in the group intervention. Compared to baseline scores, IAT-G participants recorded significantly lower mean scores on key outcome indices (mental health symptoms, adaptive stress, and functional impairment) at posttreatment and 3-month follow-up (all pairwise tests significant Ps<.05). From baseline to 3-month follow-up, score changes were greatest for functional impairment (d = 2.24), anxiety (d = 2.15) and depression (d = 1.9), followed by PTSD symptoms (d = 1.17). Interpretation : A group-based intervention designed specifically to reflect the refugee experience and adapted to the language and culture, showed positive outcomes in the context of a pragmatic, naturalistic trial implemented in a mass humanitarian emergency. Funding : United Nations High Commissioner for Refugees; National Health and Medical Research Council Australia.